Concurrent conventional & high-definition transcranial direct current stimulation for treatment of schizophrenia with co-morbid obsessive-compulsive disorder: A case report - Nayok, Swarna Buddha (Brain Stimul, 2021)
Non-invasive brain stimulation techniques such as conventional transcranial direct current stimulation (tDCS) and high definition tDCS (HD-tDCS) are increasingly being used as add-on treatment options in schizophrenia and obsessive-compulsive disorder (OCD). This is reporting of the use of a novel accelerated, symptom-specific, add-on tDCS (combining conventional and high definition) protocol in a patient with both schizophrenia and OCD. The intervention showed clinical utility by reducing both schizophrenia and OCD symptoms.